2018
DOI: 10.1039/c7cp05008a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a single water molecule on the HO2 + ClO reaction

Abstract: The catalytic effect of a single water molecule on the HO2 + ClO reaction has been investigated at the CCSD(T)/aug-cc-pVTZ//B3LYP-D3/aug-cc-pVDZ level of theory. Four H-abstraction paths and two kinds of products, among which the paths for HOCl + O2 formation are dominant, have been found for the HO2 + ClO reaction without water. The rate constant of the most favorable path for the reaction without water is computed to be 4.53 × 10-12 cm3 molecule-1 s-1 at room temperature, in good agreement with the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…While in Path RW3, the chlorine atom of ClO approaches the oxygen atom of water forming a halogen bond. The calculated optimized geometries of the ClO···H 2 O and H 2 O···ClO complexes are in accordance with the results of previous calculations [ 76 , 77 , 78 , 79 ]. Although significantly different in geometries, both configurations show similar binding energies (−2.4 and −2.8 kcal mol −1 ).…”
Section: Resultssupporting
confidence: 90%
“…While in Path RW3, the chlorine atom of ClO approaches the oxygen atom of water forming a halogen bond. The calculated optimized geometries of the ClO···H 2 O and H 2 O···ClO complexes are in accordance with the results of previous calculations [ 76 , 77 , 78 , 79 ]. Although significantly different in geometries, both configurations show similar binding energies (−2.4 and −2.8 kcal mol −1 ).…”
Section: Resultssupporting
confidence: 90%
“…In the presence of a single water molecule, both reactants are susceptible to form binary complexes with water via hydrogen bond or halogen bond interactions. , Through one of its hydrogen atoms, water clustered to DMS in one direction, exclusively, via a 2.4 Å hydrogen bond with the S atom of DMS to form DMS···H 2 O. It should be noted that this hydrogen bond with sulfur being longer than generally observed with oxygen is a result of a weaker interaction between the partial charge of the hydrogen atom and the dipole and quadrupole of the sulfur atom, as opposed to charge–charge interactions in hydrogen bonds with oxygen .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The possible reactions inside the hydrated particles have aroused great interest among researchers. The importance of water in atmospheric processes has always been concerned, but its role as a catalyst in chemical reactions is not completely elucidated and remains highly uncertain. Water could participate in atmospheric reactions by forming hydrogen bonds with reactive species, thereby having a decisive effect on their gas-phase chemistry. The study of Vöhringer-Martinez et al was one of the first to elucidate that a single water molecule could catalyze the molecule–radical reactions involving OH . Aloisio and Francisco first proposed that the photochemical properties of molecule–water complexes are different from those of individual molecules .…”
Section: Introductionmentioning
confidence: 99%
“…Du and Zhang used the CCSD­(T)/6-311++G­(3df,3pd)//BH&HLYP/6-311++G­(3df,3pd) method to calculate the rate coefficients for H 2 S and • OH reaction without and with catalyst X (X = H 2 O, (H 2 O) 2 , or H 2 S) by employing conventional transition-state theory, and they concluded that the presence of X would not play an important role in the oxidation of H 2 S by • OH radicals under atmospheric conditions . Some recent studies, however, showed inhibitive effects of water in hydrogen abstraction reactions involving ClO. Interestingly, for the reaction of CH 3 OH + ClO, the effect of water was found to be much more negative on the formation of HOCl + CH 2 OH than on the formation of HOCl + CH 3 O . For the reaction between the HCOOH···H 2 O complex and the hydroxy radical, the rate coefficient was 4 times lower than that of the bared reaction .…”
Section: Introductionmentioning
confidence: 99%